What works, why and how? A scoping review and logic model of rural clinical placements for allied health students - Anna Moran; Susan Nancarrow; Catherine Cosgrave; Anna Griffith; Rhiannon Memery (BMC, 2020)
Abstract Background Allied health services are core to the improvement in health outcomes for remote and rural residents. Substantial infrastructure has been put into place to facilitate rural work-ready allied health practitioners, yet it is difficult to understand or measure how successful this is and how it is facilitated. Methods A scoping review and thematic synthesis of the literature using program logic was undertaken to identify and describe the contexts, mechanisms and outcomes of successful models of rural clinical placements for allied health students. This involved all empirical literature examining models of regional, rural and remote clinical placements for allied health students between 1995 and 2019. Results A total of 292 articles were identified; however, after removal of duplicates and article screening, 18 were included in the final synthesis. Australian papers dominated the evidence base (n = 11). Drivers for rural allied health clinical placements include: attracting allied health students to the rural workforce; increasing the number of allied health clinical placements available; exposing students to and providing skills in rural and interprofessional practice; and improving access to allied health services in rural areas. Depending on the placement model, a number of key mechanisms were identified that facilitated realisation of these drivers and therefore the success of the model. These included: support for students; engagement, consultation and partnership with key stakeholders and organisations; and regional coordination, infrastructure and support. Placement success was measured in terms of student, rural, community and/or program outcomes. Although the strength and quality of the evidence was found to be low, there is a trend for placements to be more successful when the driver for the placement is specifically reflected in the structure of the placement model and outcomes measured. This was seen most effectively in placement models that were driven by the need to meet rural community needs and upskill students in interprofessional rural practice. Conclusion This study identifies the factors that can be manipulated to ensure more successful models of allied health rural clinical placements and provides an evidence based framework for improved planning and evaluation.